Existence of Nonradial Solutions for Hénon Type Biharmonic Equation Involving Critical Sobolev Exponents - Yajing Zhang; Ningning Wang; Yinmei Lü; Jianghao Hao (Abstract and Applied Analysis)
We prove the existence of nonradial solutions under some conditions for a semilinear biharmonic Dirichlet problem involving critical Sobolev exponents.